2012
DOI: 10.1063/1.4744986
|View full text |Cite
|
Sign up to set email alerts
|

Scale coupling in Richtmyer-Meshkov flows induced by strong shocks

Abstract: We perform the first systematic study of the nonlinear evolution and scale coupling in Richtmyer-Meshkov (RM) flows induced by strong shocks. The smoothed particle hydrodynamics code (SPHC) is employed to ensure accurate shock capturing, interface tracking and accounting for the dissipation processes. We find that in strong-shock-driven RMI the background motion is supersonic. The amplitude of the initial perturbation strongly influences the flow evolution and the interfacial mixing that can be sub-sonic or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 34 publications
10
82
0
Order By: Relevance
“…A discussion on the agreement and disagreement between compressible linear theory, based on the linearization of the Euler equations in one space dimension, and the impulsive model was discussed in (Velikovich and Dimonte 1996;Yang et al 1994). Large eddy and direct numerical simulations can greatly benefit from comparing the numerical results with theoretical results, including zero-order, linear, weakly nonlinear and highly nonlinear theories, similar to Stanic et al (2012).…”
Section: The Richtmyer-meshkov Instabilitymentioning
confidence: 99%
“…A discussion on the agreement and disagreement between compressible linear theory, based on the linearization of the Euler equations in one space dimension, and the impulsive model was discussed in (Velikovich and Dimonte 1996;Yang et al 1994). Large eddy and direct numerical simulations can greatly benefit from comparing the numerical results with theoretical results, including zero-order, linear, weakly nonlinear and highly nonlinear theories, similar to Stanic et al (2012).…”
Section: The Richtmyer-meshkov Instabilitymentioning
confidence: 99%
“…[22][23][24][25][26][27] Also, due to the conservation of tangential velocity at the rippled shock fronts, transverse velocity perturbations are generated inside the compressed fluids, which account for vorticity generation in the bulks. 23,25,[28][29][30][31][32][33][34] Cobos-Campos and Wouchuk 34,35 reported that bulk vortices with sufficiently small vorticity stabilize the interfacial instability, at least in the (compressible) linear stage. 25,[30][31][32][33][34] When the incident shock is strong and/or the amplitude of initial perturbations is large, it is known that a lot of vortices are left behind with the transmitted shock.…”
Section: Introductionmentioning
confidence: 99%
“…23,25,[28][29][30][31][32][33][34] Cobos-Campos and Wouchuk 34,35 reported that bulk vortices with sufficiently small vorticity stabilize the interfacial instability, at least in the (compressible) linear stage. 25,[30][31][32][33][34] When the incident shock is strong and/or the amplitude of initial perturbations is large, it is known that a lot of vortices are left behind with the transmitted shock. 23,26,36 These bulk vortices can interact with the interface and they affect the vorticity distribution on the interface.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The RT instability has the fastest growth rate. 11 For impulsively accelerated, mixed-material, liner-on-target pinches, i.e., those of present interest, the Richtmyer-Meshkov (RM) instability [12][13][14] may also be important. Many experimental configurations have been used to mitigate the effects of acceleration-driven RT instabilities, for example: distributing the load mass quasiuniformly (as in a large-array of fine wires), 15,16 using a gaspuff to disperse uniformly the mass distribution, 17 ensuring a high-degree of initial plasma pre-ionization, 18,19 imposing a sheared-plasma flow, 20 pre-magnetizing the pinch with an axial-magnetic field, 21,22 nesting the pinch as a series of concentric loads, to effectuate a staged-energy transfer, [23][24][25][26][27][28] etc.…”
Section: Introductionmentioning
confidence: 99%